Improved Connections for Blast-Resistant Curtain Walls - Nasseralshariati, Ehsan (Université d'Ottawa / University of Ottawa, 2023)
Curtain walls provide exterior façade to modern buildings. When subjected to blast shock waves, curtain walls may suffer significant damage, potentially causing serious injuries and casualties to building occupants. Protective films, laminated glass and strengthening of mullions and transoms are used to protect curtain wall components against blast loads. Limited research is available on blast protection of curtain wall components. On the other hand, connections of curtain wall mullions with the supporting substrate, as well as mullion-transom connections form potentially vulnerable locations under blast loads. Research on these connections is lacking in the literature. Therefore, a comprehensive research project has been undertaken in this thesis to address the behavior, analysis, and design of curtain wall connections, both between the mullions and supporting concrete slabs/beams and the mullions and transoms. The research project consists of three phases: i) Experimental research using the University of Ottawa Shock Tube as blast simulator, ii) Numerical investigation based on three-dimensional finite element method (FEM) using LS-DYNA, and iii) Non-linear dynamic analysis of curtain wall systems based on a single-degree-of-freedom (SDOF) to develop a connection design procedure. The experimental phase consisted of tests of three full-size curtain walls mounted on steel HSS sections of the Shock Tube to investigate mullion-to-transom connections and nine single mullions connected to concrete beams to investigate mullion-to-concrete substrate connection. The single mullions either represented floor-to-floor mullions or continuous mullions over the supporting slab. They were connected to concrete beams (representing floor slabs) by means of brackets, which provided high degree of rotational restraints and full translational restraints or connected through damping materials (springs or HRD rubber pads), which allowed translational movements as they dampened the effects of the shock wave. The numerical investigation involved FEM analysis and modeling of all the test specimens. The first step involved the validation of numerical models against test data. The analysis was then extended to conduct a parametric investigation to cover cases that have not been covered in the experiments. This resulted in the investigation of six different design parameters used in connection design. The numerical outcomes illustrated the importance of blast effects on connection design parameters, support reactions, curtain wall response, force and stress distributions on curtain wall components. The information gathered through experimental and numerical research on connection performance led to the formulation of a connection design procedure. Single-degree-of-freedom (SDOF) dynamic analysis technique was adopted to curtain wall analysis as a tool to compute connection design forces. Both the Uniform Facilities Criteria (UFC) charted solution (manual calculations) and two computer software developed at the University of Ottawa (RC-Blast and CW-Blast) were used to conduct SDOF analysis to validate the procedure against experimental and numerical results before they were recommended as design tools. Finally, the details of connection design are provided for different types of connections.
Keywords: Blast Resistant Curtain Wall; Curtain Wall Connection Design; Blast Load Analysis; Finite Element Method; Dampers; Shock Tube Testing